2021
DOI: 10.1016/j.isci.2021.102981
|View full text |Cite
|
Sign up to set email alerts
|

A single point mutation causes one-way alteration of pheromone receptor function in two Heliothis species

Abstract: Summary The sex pheromone processing system of moths has been a major focus of research on olfaction and speciation, as it is highly specific and closely related to reproductive isolation. The two noctuid moths Heliothis virescens and Heliothis subflexa have been used as a model for deciphering the mechanisms underlying differentiation in pheromone communication, but no information exist regarding the functions of the pheromone receptors (PRs) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…2), which is similar to the 2 Heliothis moths, H. virescens , and H. subflexa (Cao et al. , 2021). The amino acid sequences of OR11 were highly conserved among the 3 species, only slightly lower than the sequences conservation among Orco genes.…”
Section: Resultssupporting
confidence: 55%
“…2), which is similar to the 2 Heliothis moths, H. virescens , and H. subflexa (Cao et al. , 2021). The amino acid sequences of OR11 were highly conserved among the 3 species, only slightly lower than the sequences conservation among Orco genes.…”
Section: Resultssupporting
confidence: 55%
“…Our mutation studies demonstrated that a single amino acid residue substitution in two narrowly tuned ORs from the southern house mosquito can revert their specificity to the oviposition attractants skatole and indole. Amino acid residues leading to one-way alterations of insect ORs have been previously reported ( Auer et al, 2020 ; Cao et al, 2021 ; Hughes et al, 2014 ; Leary et al, 2012 ; Pellegrino et al, 2011 ; Yang et al, 2017 ; Yuvaraj et al, 2021 ). Here, we demonstrated that switching a single amino acid residue in two mosquito ORs reverses the specificity of these receptors to two physiologically and ecologically significant odorants.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, the structure for a promiscuous OR from the evolutionarily primitive (Apterygota, wingless) jumping bristletail, Machilis hrabei , MhraOR5, was solved ( DelMarmol et al, 2021 ). Although structures of ORs from winged insects (Pterygota) have not been solved to date, amino acid residues critical for OR specificity have been reported ( Auer et al, 2020 ; Cao et al, 2021 ; Hughes et al, 2014 ; Leary et al, 2012 ; Pellegrino et al, 2011 ; Yang et al, 2017 ; Yuvaraj et al, 2021 ). These studies focused on one-way alteration of specificity but did not examine how an insect detects two odorants with reverse specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Pheromone receptors (PRs) are a subset of Ors responsible for olfactory detection of sex pheromone compounds. In general, the tuning spectrum of PRs is specific [35,36]. For example, BmOr1 and BmOr3 are specifically tuned to bombykol and bombykal, respectively, in Bombyx mori [37,38].…”
Section: Introductionmentioning
confidence: 99%